Trajetória da ocupaç\~ao partidária nos setores temáticos da estrutura do Poder Executivo (1986-2016) - Noëlle da Silva; Sheila Cristina Tolentino Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This article analyzes paths and patterns of partisan appointments among sector-categories in the executive branch of Brazil from 1986 to 2016. The analysis sought to understand nuances of partisan appointments for ministries in different periods taking into consideration different presidential styles and government coalitions. We applied both qualitative and quantitative research methods and used techniques of document analysis and database construction. The methods also included a complementary discussion from recent researches on partisan ministry preferences. By analyzing partisan appointments among sector-categories, we observed two different patterns. Marked by the existence of smaller coalitions, the partisan appointments in the first period were sparse, except for the Sarney administration. The coalitions were broader in the second period, especially during the Lula and Dilma administrations, when we also observed the appearance of a structural expansion strategy. Bearing in mind the number of ministries headed by the Worker's Party (PT), we claim this strategy allowed the political party of the president to dominate both the social and government sectors. In the party-by-party analysis, Brazilian Democratic Movement Party (PMDB) stands out for its inclusion in all the administrations but it is still more concentrated in infrastructure ministries.
Keywords: Z19; 330; political party; sector-categories; ministry; partisan appointments